IMPLEMENTASI SERTIFIKASI HALAL PADA PRODUK PANGAN DI KOTA BENGKULU - Nukeriana, Debbi (UIN Fatmawati Sukarno Bengkulu, 2018)
Halal certification is a process to obtain halal certificate in accordance with Islamic Shari’ah it, aims to provide legal certainty of the halalness of a product so that it can reassure the heart for those who consume it. This study is motivated by the number of food producers in Bengkulu City who do not do halal certification. This research raised the problem about the implementation of halal certification, supporting and inhibiting factors and the role of LPPOM MUI of Bengkulu Province in im- plementing halal certification on food products in Bengkulu City. The purpose of this research is to analyze the implementation of halal certification, identify the supporting and inhibiting factors and to explore and find the role of LPPOM MUI of Bengkulu Province in implementing halal certification on food products in Bengkulu City. This type of research is a field research using a sociological juridical approach that examines the applicable legal provisions and what happens on the ground. In collecting the data the research used interviews and document studies. The technique of data analysis is descriptive qualitative by way of interpretation, triangulation and content analysis. From the research result, it can be concluded that first, the implementation of halal certification on food products in Bengkulu City has been implemented although still a small part of the number of Small and Medium Industry (IKM) in Bengkulu City. Secondly, the supporting factor for the implementation of halal certification in food products in Bengkulu City is to provide a sense of comfort and confidence in a product, consumers of majority food are Muslim and increase income / turnover of food producers. As for the inhibiting factors are the Law on Halal Product Guarantee is still voluntary (voluntary), lack of information / knowledge about halal certification and constrained halal certification cost. Third, the Role of LPPOM MUI of Bengkulu Province in the implementation of halal certification on food products in Bengkulu City is to protect the public against illicit products. It also provides socialization of halal certification either through formal means such as training and socialization or unofficially such as to family, friends and friends